2021
DOI: 10.2478/johr-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Good Agricultural Practice to Increase Yield and Profit of Ginger Farming in Nepal

Abstract: Ginger (Zingiber officinale) is one of the major high-value cash crops in Nepal. Low yield, conventional farming, and limited access to production resources such as improved cultivars, production technologies, and extension services are the existing problems of Nepali ginger farmers. In this study, we conducted community based-participatory research in Ilam district, Nepal, in 2015–2017. This research aimed to explore the appropriate ginger farming technology considering yield, income, and environment. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…However, there were no yield differences among the three planting material types stored in flats (Table 8). Our yields of 21,897 kgÁha -1 for MS transplants in 2020 (Table 7) and 20,152.4 kgÁha -1 for MS from pans in 2019 (Table 8) are also comparable to the 17,900 and 24,590 kgÁha -1 of rhizome harvest obtained in tropical field locations using 60 g or greater rhizome pieces (Baral et al 2021;Beale et al 2006). Contrary to the results of Prasath et al (2018), which showed no significant difference between the yield of twosprout transplants, single-sprout transplants, and conventional seed rhizomes in 7 months of tropical weather, our study showed SS transplants produced significantly lower yields than the larger seeded rhizomes.…”
Section: Resultssupporting
confidence: 75%
“…However, there were no yield differences among the three planting material types stored in flats (Table 8). Our yields of 21,897 kgÁha -1 for MS transplants in 2020 (Table 7) and 20,152.4 kgÁha -1 for MS from pans in 2019 (Table 8) are also comparable to the 17,900 and 24,590 kgÁha -1 of rhizome harvest obtained in tropical field locations using 60 g or greater rhizome pieces (Baral et al 2021;Beale et al 2006). Contrary to the results of Prasath et al (2018), which showed no significant difference between the yield of twosprout transplants, single-sprout transplants, and conventional seed rhizomes in 7 months of tropical weather, our study showed SS transplants produced significantly lower yields than the larger seeded rhizomes.…”
Section: Resultssupporting
confidence: 75%
“…Similarly, determinants of adoption of agricultural intensification under different cropping system have assessed by Raut et al (2011). The field trials on influence of different good agriculture practices were carried out by various researchers including Baral et al (2021) but adoption determinants such as demographic, socio-economic, and resource accessibility factors were not studied. There are many impediments on adoption of SAPs by resource poor farmers, possible endo and exogenous determining factors should be studied and results should be integrated during policy formulation and implementation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the market, ginger as a commodity takes in various forms. Ginger products come as fresh or powdered, in oils or preserved, dried or pickled, as tea, syrup, or in crystallized form (Baral, 2021). Driving forces for global demand for ginger are health consciousness, population growth, changing social structure, and lifestyle.…”
Section: Introductionmentioning
confidence: 99%